Comparison of Contrast Sensitivity and Through Focus in Small-Aperture Inlay, Accommodating Intraocular Lens, or Multifocal Intraocular Lens Subjects - Garcia-Gonzalez, Montserrat; Teus, Miguel A. (American journal of ophthalmology, 2016)
[...]the main conclusion of the study is that KAMRA inlay provides better results than premium IOLs in terms of contrast sensitivity and distance and intermediate vision.